Developing SMEs as environmental businesses. Issue 1 (4th January 2016) - Onyido, Tochukwu Ben C.; Boyd, David; Thurairajah, Niraj
Abstract : Purpose: – The purpose of this paper is to establish opportunities for small- and medium-sized enterprises (SMEs) to become environmental businesses. The "Environmental Business" concept refers to a commercial organisation that provides goods and/or services which provide socio-environmental value and which are produced in such a way that the organisation addresses environmental and social problems. Design/methodology/approach: – Interviewing and observation were used to conduct a case study of how 30 SMEs prepared for the UK's Green Deal programme in the West Midlands County, UK. In total, 20 interviews were conducted and 23 field notes were recorded. Based on the literature review, the research enquiry into practice, and the philosophical approach of pragmatism adopted by the research, a "Three Ps" (profit, process and product) analytical framework was established with which to operationalise the environmental business. Findings: – The research identifies tactical opportunities that assist SMEs to function as environmental businesses whilst maintaining the traditional focus on economic performance. It also shows the benefits and challenges involved. Research limitations/implications: – The research focused on a case study related to specific sectors (building and energy) within a specific UK region (West Midlands), which limits the generalisability of the results. Practical implications: – The research highlights practical opportunities for SMEs to address existing environmental and social problems through their products and processes and prevent new problems arising due to their operations. Originality/value: – This research represents an initial step in developing a pragmatic implementation model by which SMEs can overcome barriers to being environmental businesses whilst maximising business advantages.